Literatur Review: Tingkat Kelimpahan Ikan Karang di Perairan Indonesia - Khairunisak Khairunisak; Vania Fachreyna Morhaban; Firdus Firdus; Muhammad Nasir; Zainal Abidin Muchlisin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The condition of coral fish will improve if the health of coral reefs has a direct impact on the abundance of coral fish. The literature review aims to identify coral fish species and the abundance of individual coral fish in Indonesian waters. This study is a literature review containing journal articles from 2010 to 2024 from the Google Scholar database. The results of the study show that the coral fish species found in Indonesian waters include Acanthuridae, Scaridae, Haemulidae, Mullidae, Lutjanidae, Caesionidae, Serranidae, Siganidae, Sphyraenidae, Pomacentridae, Chaetodontidae, Mullidae, Muraenidae, Nemipteridae, Apogonidae, Balistidae, Labridae, Aulostomidae, Carangidae, Holocentridae, Pemoheridae, Pomachantidae, Siganidae, Tetraodontidae, and Zanclidae. The highest abundance of coral fish in Indonesian waters is found in the waters of the Karimunjawa National Park Conservation area with the highest abundance value of 14,850 ind/ha, namely from the Pomacentridae family with factors that influence the abundance of coral fish in Indonesian waters in the form of environmental conditions, coral reef cover values, substrate morphological characteristics, and community activities.